Hubungan Antara Dukungan Sosial Teman Sebaya Dan Resiliensi Akademik Terhadap Kecemasan Mahasiswa Tingkat Akhir Dalam Menyusun Skripsi - Desta Setiasih; Dewi Lutfianawati; Vira Sandayanti (Program Studi Psikologi Islam, 2026)
Thesis anxiety is a psychological condition characterized by excessive worry, nervousness, and fear when facing a final assignment. This study aims to determine the effect of peer social support and academic resilience on academic anxiety in final-year students when writing their theses. This study used a quantitative approach with a correlational method. The subjects were final-year students at Malahayati University, Bandar Lampung, selected using a quota sampling technique. The research instruments included an academic anxiety scale, a peer social support scale, and an academic resilience scale. The results showed that simultaneously, peer social support and academic resilience significantly influenced academic anxiety, with an effective contribution of 87.6%. Partially, peer social support and academic resilience both had a significant influence on academic anxiety. Academic resilience was the most dominant factor in reducing anxiety in final-year students. These findings confirm that the combination of social support and academic resilience plays a crucial role in helping students cope with the pressures of thesis writing. Keywords: academic anxiety, peer social support, academic resilience, final-year students, thesis. Keywords : academic anxiety, peer social support, academic resilience, thesis